Edukacja religijna w Anglii – budowanie spójności społecznej i obywatelskiej w warunkach pluralizmu kulturowego - Hejwosz-Gromkowska, Daria (Wydawnictwo Naukowe UAM, 2017)
Faith institutions play a vital role in shaping social structure, social capital and social cohesion. Both religious and citizenship education can contribute to making good citizens. The latter is more political oriented, while the former is focused on faith, spirituality and morality. The English model of religious education is oriented towards a multi-faith dialogue, without the aspects of worship and confession. The phenomenological approach assures that every child, regardless of their religious background, is obligated to attend religious education. Today, the UK is facing many challenges, including secularization and cultural differentiation of the society. Thus, the educational institutions revise curricula and aims of learning. The aim of the paper is to present and analyze the main premises of educational policy in the context of religious education in public schools in England. I will also attempt to reconstruct the social and political ongoing debate on the aims of RE.
Religious Education in England – Building Social Cohesion and Citizenship in the Plural Society
Keywords: citizenship education; religious education; England; multiculturalism